Neutrophil and platelet to lymphocyte ratio in patients with hypothyroid hashimoto’s thyroiditis - Önalan, Erhan; Dönder, Emir (Mattioli 1885, 2020)
Aim: Chronic lymphocytic thyroiditis is among the most common causes of hypothyroidism along with HT (Hashimoto’s thyroiditis) goitre, which is also named as autoimmune thyroiditis. Our study aims to determine the usefulness of PLR (platelet to lymphocyte ratio) and NLR (neutrophil to lymphocyte ratio), which can be obtained with a hemogram, at the clinical course or the severity of the disease in patients with Hashimoto’s thyroiditis. Materials and Methods: Our study is a retrospective cross-sectional study that included 121 hypothyroid or subclinical hypothyroid Hashimoto’s thyroiditis patients and a healthy control group comprised of 100 individuals. Thyroid-stimulating hormone (TSH), free triiodothyronine (FT3), free thyroxine (FT4), anti-thyroid peroxidase (anti-TPO), complete blood count (CBC), and C-reactive protein (CRP) results were obtained from patient files for both HT patients and the control group, and we computed PLR and NLR for both groups. Results: PLR was lower in patients diagnosed with HT compared to the healthy control group, with statistical significance (respectively, 130.8±50.5 versus 145.3±58.5; p<0,05). NLR was higher in patients diagnosed with HT compared to the control group and a statistically significant relationship was determined (respectively, 2.43±0.94 versus 2,11±0,81; p<0,05). In addition to the present findings, we determined that PLR and NLR were correlated with anti-TPO, TSH, and FT4, although without statistical significance. Conclusion: As values that can be measured with an inexpensive and easily accessible routine hemogram, PLR and NLR can serve as practical and valuable markers at the clinical course or the severity of the disease and other diseases that are autoimmune and progress with chronic inflammation. © Mattioli 1885.
Keywords: Hashimoto’s thyroiditis; Neutrophil/lymphocyte ratio; Platelet/lymphocyte ratio